2018
DOI: 10.1080/21548331.2018.1464872
|View full text |Cite
|
Sign up to set email alerts
|

Point prevalence survey of antibiotic use and resistance at a referral hospital in Kenya: findings and implications

Abstract: Whilst the dosing of antibiotics seemed adequate, there was high use of antibiotics in this hospital. This needs to be urgently reviewed with currently appreciable empiric antibiotic use. Programmes are being instigated to address these concerns. This includes developing antibiotic guidelines and formularies especially for empiric use as well as implementing antimicrobial stewardship activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
66
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 39 publications
(35 reference statements)
21
66
2
Order By: Relevance
“…The results of the PPS in three hospitals from different levels of healthcare in Tanzania showed a prevalence of antibiotic use in hospital inpatients of 44%. This is comparable to results from African countries in the Global PPS (50%) as well as surveys from individual sub-Saharan African countries such as Botswana 70.6% [18] and Kenya 67.7% [15].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The results of the PPS in three hospitals from different levels of healthcare in Tanzania showed a prevalence of antibiotic use in hospital inpatients of 44%. This is comparable to results from African countries in the Global PPS (50%) as well as surveys from individual sub-Saharan African countries such as Botswana 70.6% [18] and Kenya 67.7% [15].…”
Section: Discussionsupporting
confidence: 83%
“…Recently, a PPS performed among hospitals throughout Botswana found a high prevalence (70.6%) of antimicrobial use, as well as different areas for improvement [14]. A PPS performed in a referral hospital in Kenya reported comparable ndings [15].…”
Section: Introductionmentioning
confidence: 95%
“…However, again this needs further investigation [56]. In this study, the highest use of antibiotics was seen in ICU which was similar to the results observed in Kenya and Switzerland [35,57], with high rates of antibiotic use in ICUs seen in the recent PPS study in Pakistan [37]. Overall, the extensive use of broad-spectrum antibiotics in de nitive treatment could be explained by high bacterial resistance rates [58].…”
Section: Discussionsupporting
confidence: 79%
“…Choudhary et al also found that a change of therapy was only undertaken in 20.9% of positive culture patients. We are aware that there can be challenges with ordering culture reports among hospitals in LMICs with high rates of empiric prescribing [34][35][36][37][38]. However, we are aware that the results of culture reports can help reduce the number of antibiotics prescribed, with Berild et demonstrating a 22% reduction consumption of antibiotics with de nitive treatment [25].…”
Section: Introductionmentioning
confidence: 99%
“…Half of the respondents stated that therapeutic interchange policies were the responsibility of PTCs, with PTCs generally considered the most ideal setting for such programmes, which is encouraging as they can ensure that any guidelines are based on scientific evidence and any national Essential Medicine List [17,[37][38][39]. Several actions were reported as part of the pharmacist's practice during substitution (Table 5) including communication with other health professionals and providing information on available alternatives.…”
Section: Discussionmentioning
confidence: 99%